Case Reports of Extracorporeal Treatments in Poisoning: Historical Trends. Issue 4 (14th May 2014) - Mardini, Joelle; Lavergne, Valery; Roberts, Darren; Ghannoum, Marc
Abstract There are currently limited data on the trends in case reporting of poisoned patients undergoing enhanced elimination with an extracorporeal treatment (ECTR). The present manuscript specifically reviews the longitudinal trends of reports according to technique, poison, and country of publication. To identify case reports of ECTR use in the management of poisoning, multiple databases were searched. There were no limitations on language and year of publication. All case reports describing individual patients undergoing ECTR with the intent of enhancing the elimination of a poison were included in the analysis. Since 1913, 2908 reports were identified. There were an increasing number of published reports with time except for a slight decrease during the 1990s. Hemodialysis was by far the most commonly used ECTR in poisoning, followed by hemoperfusion. The number of reported peritoneal dialyses decreased steadily since 1980s. Methanol, ethylene glycol, lithium, and salicylates remained among the most commonly reported poisons in every decade. The large majority of publications originated from either Europe or North America, and more specifically from the United States, Germany, the United Kingdom, and China. Despite the emerging apparition of new techniques, hemodialysis remains to this day the favoured ECTR in the treatment of poisoned patients.